Long‐term outcome of kidney transplant by using restored kidney grafts after tumour ex vivo excision – a prospective study. (20th July 2020) - He, Bulang; Ng, Zi Qin; Mou, Lingjun; Delriviere, Luc; Jaques, Bryon; Tuke, Jonathan; Musk, Gabrielle C.; Lim, Wai
Summary: The aim of this study is to report long‐term outcomes of kidney transplantation by using the kidney graft after a small tumour ex vivo excision. A structured programme was established to use the restored kidney graft from urological referral after radical nephrectomy. The criteria were defined as tumour size ≤3 cm, margin clear on frozen section and recipients aged ≥60 years or those on the urgent list for transplantation as a result of imminent lack of dialysis access. The recipients were followed up regularly for surveillance of tumour recurrence. Between February 2007 and February 2018, 28 recipients had kidney transplantation by using the restored kidney grafts. The tumour size was 2.6 ± 0.7 cm. The follow‐up was median 7 years without evidence of tumour recurrence. The patient and graft survival was satisfactory. Kidney transplantation by using restored kidneys after a small tumour excision is a novel source for selected recipients. The long‐term patient and graft survival is satisfactory. Although there is a risk of tumour recurrence, it is rare event. Together with literature review, we would support use of kidney graft after a small tumour excision for selected recipients.